The interaction of fragment 1 of prothrombin with the membrane surface is a prerequisite for optimum expression of factor Va cofactor activity within prothrombinase - Bukys, Michael A.; Orban, Tivadar; Kim, Paul Y.; Nesheim, Michael E.; Kalafatis, Michael (Thrombosis and Haemostasis, 2008)
Incorporation of factor (F) Va into prothrombinase directs prothrombin activation by FXa through the meizothrombin pathway, characterized by initial cleavage at Arg320 We have shown that a pentapeptide with the sequence DYDYQ specifically inhibits this pathway. It has been also established that Hir54–65(SO3 -) is a specific inhibitor of prothrombinase.To understand the role of FVa within prothrombinase at the molecular level, we have studied thrombin formation by prothrombinase in the presence of various prothrombin-derived fragments alone or in combination. Activation of prethrombin 1 is slow with cleavages at Arg320 and Arg271 occurring with similar rates. Addition of purified fragment 1 to prethrombin 1 accelerates both the rate of cleavage at Arg320 and thrombin formation.Both reactions were inhibited by Hir54–65(SO3 -) while DYDYQ had no significant inhibitory effect on prethrombin 1 cleavage in the absence or presence of fragment 1. Similarly, activation of prethrombin 2 by prothrombinase,is inhibited by Hir54–65(SO3 -), but is not affected by DYDYQ.Addition of purified fragment 1•2 to prethrombin 2 accelerates the rate of cleavage at Arg320 by prothrombinase. This addition also results in a significant inhibition of thrombin formation by DYDYQ and is concurrent with the elimination of the inhibitory effect of Hir54–65(SO3 -) on the same reaction. Finally, a membrane-bound ternary complex composed of prethrombin 2/fragment 1•2/Hir54–65(SO3 -) is inhibited by DYDYQ. Altogether,the data demonstrate that membrane- bound fragment 1 is required to promote optimum FVa cofactor activity which in turn is translated by efficient initial cleavage of prothrombin by prothrombinase at Arg320.
Keywords: Prothrombin; thrombosis; factor Va; blood coagulation